Cochlear Implantation Outcomes in Patients With OTOF Mutations - Zheng, Dandan; Liu, Xiao (Frontiers in Neuroscience, 2020)
Auditory neuropathy is a special term of hearing loss caused by dysfunction of the synapse of the inner hair cells and auditory nerve, and/or the auditory nerve itself. For patients with auditory neuropathy who have severe to profound hearing loss or failed auditory skills development with hearing-aids, cochlear implantation (CI) serves as the only possible effective treatment. It is accepted that the exact sites of lesion causing auditory neuropathy determine the CI performance. Mutations in OTOF gene were the first identified and the most common cause of congenital auditory neuropathy. The site of lesion in patients with auditory neuropathy caused by biallelic OTOF mutations (OTOF-related auditory neuropathy) is presumed to be presynaptic, leaving auditory nerve function intact. Thus, OTOF-related auditory neuropathy is expected to have good CI performances. In this review, we describe the CI outcomes in patients with OTOF-related auditory neuropathy. We will focus on whether biallelic OTOF mutations are ideal indications for CI in patients with auditory neuropathy. Also, the factors that may still influence the CI outcomes in OTOF-related auditory neuropathy are discussed.